Anaerobic digestion of a fish processing industry sludge - Carvalho, L. (2012)
Due to the fact that all fish processing plants operating in Portugal send their sludge from the wastewater treatment process to landfill, and because it is a costly management policy, the aim of this work was to assess the potential use of this substrate for the production of biogas through the anaerobic process technology. Anaerobic digestion has long proven to be an efficient way for the production of a renewable fuel – Biogas - that can be used as a source of energy to produce electricity and heat. This renewable energy resource can be used to reduce the plant processing costs, reducing also the industry carbon footprint. So, the produced sludge becomes a valuable sub-product of the wastewater treatment process instead of being considered a waste, with disposal costs associated. In this study we performed mesophilic (35 ± 1°C) batch assays during 51 days. The inoculum used was from an anaerobic digester operating in a municipal WWTP, also at mesophilic conditions. The anaerobic digestion of the fish sludge produced 700 m3 of CH4/ton SV, which is a really promising result.